Molecular Brain - Kaang, Bong-Kiun; Bliss, Tim; Miyakawa, Tsuyoshi; England, Emily; Zhuo, Min
Molecular Brain is an open access, peer-reviewed journal that considers manuscripts on all aspects of studies on the nervous system at the molecular, cellular, and systems level providing a forum for scientists to communicate their findings. Molecular brain research is a rapidly expanding research field in which integrative approaches at the genetic, molecular, cellular and synaptic levels yield key information about the physiological and pathological brain. These studies involve the use of a wide range of modern techniques in molecular biology, genomics, proteomics, imaging and electrophysiology.